Sources and Occurrence of Cyanotoxins Worldwide - Pelaez, Miguel; Antoniou, Maria G.; He, Xuexiang; Dionysiou, Dionysios D.; De La Cruz, Armah A.; Tsimeli, Katerina; Triantis, Theodoros; Hiskia, Anastasia; Kaloudis, Triantafyllos; Williams, Christopher R.; Aubel, Mark; Chapman, Andrew; et al. (My University, 2009)
The eutrophication of water resources, mainly attributed to antrophogenic activities such as sewage and agricultural runoffs, has led to a worldwide increase in the formation of cyanobacterial harmful algal blooms (Cyano-HABs). Cyano-HABs have the ability to produce and release toxic compounds, commonly known as cyanotoxins, which comprise a potent threat for human and animal health as well as negative economical impacts. This chapter presents an overview on the sources and occurrence of species of cyanobacteria and their association with the production of cyanotoxins throughout the world. The main bloom-forming cyanobacteria that have been detected include Microcystis, Cylindrospermopsis, Anabaena, Aphanizomenon, and Planktothrix. The main cyanotoxins related to these cyanobacteria are microcystins, cylindrospermopsin, anatoxin-a and saxitoxins.
Keywords: Zebra Mussel; Cyanobacterial Bloom; Microcystis Aeruginosa; Microcystin Concentration; Cyanobacterial Toxin